Self‐Regulatory Efficacy Encourages Exercise Persistence Despite Arthritis Flare Symptoms. Issue 3 (31st August 2017) - Sessford, James D.; Brawley, Lawrence R.; Cary, Miranda A.; Flora, Parminder K.; Blouin, Jocelyn E.; Meade, Laura; Strachan, Shaelyn M.; Gyurcsik, Nancy C.
Abstract : Background: The study of exercise adherence during an arthritis flare is recommended by arthritis researchers. Studies to date have been correlational. Methods: Social cognitions of exercising individuals with arthritis who consider exercise adherence under different levels of challenge of an arthritis flare were examined using an experimental design. Exercising individuals with differential self‐regulatory efficacy for managing arthritis flare symptoms (SRE‐flare) were randomly assigned to conditions where flare symptoms were perceived as either many or few. Individuals in each condition responded about the strength of their anticipated persistence to continue exercise, and their self‐regulatory efficacy to use coping strategies to enable exercise. Results: Higher SRE‐flare individuals expressed significantly (a) greater persistence (Cohen's d = 1.17) and (b) more confidence to use their flare coping solutions (Cohen's d = 1.44). Conclusion: Main findings were as hypothesised. When exposed to the condition with more limiting flare symptoms (i.e. greater challenge), high SRE participants were the most confident in dealing with flare symptoms and exercising. Identifying lower SRE‐flare individuals less likely to persist with exercise during arthritis flares may improve tailored exercise counselling.